Negative work-to-family spillover stress and heightened cardiovascular risk biomarkers in midlife and older adults - HARTANTO, Andree (Institutional Knowledge at Singapore Management University, 2024)
Objectives: The current study aimed to investigate the health implications of negative work-to-family spillover on cardiovascular risk biomarkers. Methods: In a large-scale cross-sectional dataset of working or self-employed midlife and older adults in the United States (N = 1179), we examined five biomarkers linked to cardiovascular risk, including high-density lipoprotein (HDL) cholesterol, low-density lipoprotein cholesterol, triglyceride, interleukin-6, and C-reactive protein. Negative work-to-family spillover, measured using a four-item self-reported questionnaire, was included into our model to study its association with these cardiovascular risk biomarkers. Results: Our findings indicate a significant association between negative work-to-family spillover and cardiovascular risk biomarkers – higher triglycerides (β = 0.108, p Conclusions: The current study supports the premise that spillover of work-related tensions into family life is associated with objective physiological changes that contribute to cardiovascular risk.